The influence of socio-demographic factors on work performance among employees of government agricuture agencies in Malaysia. - Mohamed Shaffril, Hayrol Azril; Uli, Jegak (Journal of International Social Research, 2010)
Work performance has been identified as the significant key for organizations to gain competitive advantage and superior productivity. Thus, this study intends to discover what exactly affect work performance among employees of government agriculture agencies in Malaysia. A total of 180 employees were selected as the respondents for this study. The respondents were chosen from ten government agriculture agencies in Malaysia. From the ANOVA and independent t-test conducted, type of residential house was found to have significant difference with work performance while Pearson Correlation employed indicated that age, working experience and gross monthly salary has significant and positive relationship with work performance.